2015
DOI: 10.1002/ptr.5382
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐diabetic and Anti‐hyperlipidemic Effects and Safety ofSalacia reticulataand Related Species

Abstract: Extracts of Salacia reticulata Wight (Hypocrataceae) roots, stems, and leaves have been used in Asia for hundreds of years for the folkloric treatment of diabetes and other health problems. Constituents that have been identified as exhibiting anti‐diabetic effects include salacinol, kotalanol, ponkorinol, salaprinol, and their corresponding de‐0‐sulfonated compounds. Mangiferin, kotalagenin 16‐acetate and various proanthocyanidin oligomers have also been isolated. Studies indicate that Salacia extracts modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…Historical and present uses of Salacia in India and Japan show that this herbal extract is used as a nutritional adjunct, either as a tea or supplement, taken with meals for its antidiabetic properties. Salacia reticulata [ 23 , 26 32 ] and Salacia oblongata [ 33 , 34 ] do lower postprandial glycaemia in patients with type 2 diabetes and metabolic risk factors [ 35 37 ]. Salacia chinensis with a meal suppressed the increases of postprandial blood glucose at 30 minutes after meal.…”
Section: Discussionmentioning
confidence: 99%
“…Historical and present uses of Salacia in India and Japan show that this herbal extract is used as a nutritional adjunct, either as a tea or supplement, taken with meals for its antidiabetic properties. Salacia reticulata [ 23 , 26 32 ] and Salacia oblongata [ 33 , 34 ] do lower postprandial glycaemia in patients with type 2 diabetes and metabolic risk factors [ 35 37 ]. Salacia chinensis with a meal suppressed the increases of postprandial blood glucose at 30 minutes after meal.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, cordifolioside A is reported to improve insulin signaling and hepatic metabolism during insulin resistance. Further, it is reported to lower the blood glucose and cholesterol level [19] . Magnofl orine is reported to have a direct effect on carbohydrate metabolism, increase the insulin sensitivity and reverse diabetes-associated alterations in lipid profi le and oxidative stress [20] .…”
Section: Drug-likeness Character (Lipinski's Rule Of Fi Ve)mentioning
confidence: 98%
“…Various other plant extracts may enhance thermogenesis when combined with well-known thermogenic agents. Studies have shown that aqueous extracts of S. reticulata modulate glucose and lipid metabolism through multiple mechanisms (Stohs and Ray, 2015). Extracts of the seeds of S. indicum have also been shown to modulate lipid metabolism (Biswas et al, 2010;Asgary et al, 2013).…”
Section: Combination Productsmentioning
confidence: 99%